The Relationship Between Parental Knowledge Levels and the Intensity of Giving Gadgets to Preschool-Aged Children.: Relationship Between Parental Knowledge Levels and the Intensity of Giving Gadgets to Preschool-Aged Children. - Putri, Prestasianita; Tri Afandi, Alfid; Yunita Lestari, Indah (International Journal of Midwifery and Health Sciences, 2025)
The increasing use of gadgets among preschool-aged children has become a growing concern for parents and educators. This study examines the relationship between parental knowledge levels and the intensity of gadget usage given to preschool-aged children. A cross-sectional design was employed, involving 52 parents of preschool-aged children selected through purposive sampling in an urban community. Data were collected using structured questionnaires that assessed parental knowledge levels regarding gadget usage and the frequency with which gadgets were provided to their children. Parental knowledge was categorized as either "adequate" or "inadequate," while gadget usage intensity was measured based on daily screen time reported by the parents. Statistical analysis was performed using Spearman's rank correlation test to determine the association between the two variables. The results revealed a significant relationship between parental knowledge levels and the intensity of gadget usage (p = 0.017). Parents with inadequate knowledge were more likely to allow higher gadget usage among their children compared to those with adequate knowledge. These findings suggest that enhancing parental awareness and understanding of the potential risks associated with excessive gadget exposure is crucial in promoting healthier developmental environments for preschool-aged children. Future interventions should focus on educating parents about appropriate gadget use and alternative activities to minimize screen time and support optimal child development.